Factors Affecting Librarian Job Satisfaction in Selected Universities in Malaysia - Jounaidi, Abd Alrahman Mhd Ramezal (جامعة المدينة العالمية, 2016)
The purpose of this study is to determine what selected factors are related to library job satisfaction at selected Malaysian universities. A comprehensive survey using questionnaire was used to collect data from the libraries worker in academic Malaysian universities who were the population of this study. A total of 185 usable questionnaires distributed to the respondents by (online and by hand) were received, the sampling method of my study was selected on the basis of convenience sample. The finding of this sample of workers only offers partial support of the cognitive evaluation theory that the researcher will depend on it finding what are the extrinsic and intrinsic factors that affect librarian job satisfaction .This study shows that motivator factors such as culture, working environment and supervision are related to job satisfaction. The evidence from this study suggests a negative correlation of /salary and job satisfaction which supports the findings of other previous studies. This study also suggests that cultural background differences may have an impact on employee’s reaction to job satisfaction, as the pattern of job attitudes for workers at Malaysian library may have not similar to other previous studies that in the cognitive evaluation theory. The study also explored job satisfaction in regard to selected factors such as: gender, age, level of education, position job and , this study has a number of practical implications towards academic and industry of the staff library, the study recommended that the management of university libraries should develop and sustain policies that will enhance factors of job satisfaction, such as: culture factor perception , culture, /salary, supervision and work environment, so that they can discharge better services to library users, in order to enhance productivity of the staff and accomplish the institutional objectives. In addition, the management should attempt to provide a level playing for equal opportunities between user librarians by ensuring that basic needs for academic excellence are provided for all, irrespective of gender, so that the user staff will equally derive satisfaction In their working place.
Keywords: ماليزيا -- المكتبات الجامعية -- الرضا الوظيفي -- أخصائيو المكتبات